The Meditative Nature of Folklore of Turkic Peoples (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
The article justifies the direct connection of editorial lyrics with the social period and cultural environment. In the Uzbek folk ritual songs, universal human problems such as the transience of the world, the fact that a person who has left this world does not return, and a great educational lesson are interpreted with examples.